Identification of neisserial DNA binding components - Lång, Emma (Microbiology Society, 2009)
Neisseria meningitidis, a causative agent of meningitis and septicaemia, expresses type IV pili, a feature correlating with the uptake of exogenous DNA from the environment by natural transformation. The outer membrane complex PilQ, through which pili are extruded and retracted, has previously been shown to bind DNA in its pore region. In order to further elucidate how DNA is transported across the membranes, we searched for DNA binding proteins within the meningococcal inner membrane. Inner membrane fractions from a panel of neisserial strains were subjected to a solid-phase overlay assay with DNA substrates, and MS was subsequently employed to identify proteins that bind DNA. A number of DNA binding components were detected, including the pilus biogenesis component PilG, the competence protein ComL, and the cell division ATP-binding protein FtsE, as well as two hypothetical proteins. The DNA binding activity of these components was not dependent on the presence of the neisserial DNA uptake sequence. Null mutants, corresponding to each of the proteins identified, were constructed to assess their phenotypes. Only mutants defective in pilus biogenesis were non-competent and non-piliated. The DNA binding activity of the pilus biogenesis components PilQ and PilG and the phenotypes of their respective null mutants suggest that these proteins are directly involved as players in natural transformation, and not only indirectly, through pilus biogenesis.